Increasing fish production from wetlands at Lake Victoria, Uganda using organically manured seasonal wetland fish ponds - Kaggwa, Rose C.; Anne, A. van Dam; Balirwa, John S.; Kansiime, Frank; Patrick, Denny (Wetlands ecology and management, 2009)
The processes driving primary productivity and its impacts on fish production were investigated in field trials in eight seasonal earthen wetland ponds ‘Fingerponds’ (192 m2) in Uganda between 2003 and 2005. The ponds were stocked by the seasonal flood with predominantly Oreochromis spp. at densities ranging from 0.1 to 0.5 fish m−2. Chicken manure (521, 833 or 1,563 kg ha−1) was applied fortnightly. Results showed that primary productivity was enhanced with maximum average net primary productivity (±Standard Error) of 11.7 (±2.5) g O2 m−2 day−1 at the Gaba site and 8.3 (±1.5) g O2 m−2 day−1 at the Walukuba site. Net fish yields were higher in manured ponds with up to 2,670 kg ha−1 yield for a 310 day growth period compared to less than 700 kg ha−1 in unmanured ponds. Fish production was limited mainly by high recruitment, falling water levels, light limitation from high suspended solids and turbidity, and low zooplankton biomass. It was concluded that Fingerponds have a high potential for sustainable fish production and can contribute to the alleviation of protein shortages amongst the riparian communities around Lake Victoria. Production can be enhanced further with improved stock management.